العنف المدرسى من وجهة نظر تلاميذ السنة الرابعة متوسط - غراب,يمينة; الصيفي,مليكة (University of Eloued جامعة الوادي, 2024)
The study addressed the subject of school violence from the perspective of a fourth average student and aimed to learn about the causes and manifestations of school violence and to identify the factors leading to school violence. Using the descriptive approach in the study. We applied the school violence questionnaire adopted by "Two Students or Hana Hamed and Hina Ben Omar in their studies" to a meaningful sample of four middle students. The results of the study were as follows: There is an internal correlation of a statistical function between the dimensions of the first axis and the most common types of violence from the perspective of the fourth average pupil and the overall degree of the axis. There is an internal correlation of statistical function between the dimensions of the second axis, which is responsible for the prevalence of the phenomenon of school violence from the perspective of the fourth to the total degree of the axis. There is also an internal correlation of statistical function between the dimensions of the third axis and the factors leading to the prevalence of the phenomenon of school violence from the perspective of the fourth average pupil and the overall degree of the axis. There is an internal correlation of a statistical function between the dimensions of the fourth axis and the persons who are used by pupils when they are subjected to violence from the perspective of the fourth . تناولت الدراسة موضوع العنف المدرسي من وجهة نظر تلاميذ الرابعة متوسط وهدفت الى معرفة اسباب ومظاهر العنف المدرسي والتعرف على العوامل المؤدية الى العنف المدرسي مستخدمين المنهج الوصفي في الدراسة. حيث قمنا بتطبيق استبيان العنف المدرسي من طرف الطالبتين ام الهنا حامد وهنية بن عمر في دراستهم على عينة قصدية من تلاميذ رابعة متوسط وتوصلت نتائج الدراسة الى: يوجد اتساق ارتباطي داخلي دال احصائيا بين ابعاد المحور الأول انواع العنف الأكثر انتشارا من وجهة نظر تلاميذ الرابعة متوسط والدرجة الكلية للمحور ، ويوجد اتساق ارتباطي داخلي دال احصائيا بين ابعاد المحور الثاني المسؤول عن انتشار ظاهرة العنف المدرسي من وجهة نظر تلاميذ الرابعة متوسط والدرجة الكلية للمحور . كذالك يوجد اتساق ارتباطي داخلي دال احصائيا بين ابعاد المحور الثالث العوامل التي تؤدي إلى تفشي ظاهرة العنف المدرسي من وجهة نظر تلاميذ الرابعة متوسط والدرجة الكلية للمحور ، ويوجد اتساق ارتباطي داخلي دال احصائيا بين ابعاد المحور الرابع الأشخاص الذين يلجأ إليهم التلاميذ عند تعرضهم للعنف المدرسي من وجهة نظر تلاميذ الرابعة متوسط والدرجة الكلية للمحور ، واخيرا لا توجد فروق دالة احصائيا بين وجهتي نظر الذكور والإناث من تلاميذ الرابعة متوسط على مقياس العنف المدرسي.
Keywords: العنف المدرسي; school violence